Correlation of Self-Confidence and Student Learning Motivation Against Learning Outcomes of Class X Digital Simulation - Radyuli, Popi; Wijaya, Indra; Ulfina, Ita (Journal of Education Reseach and Evaluation, 2020)
This study aims to determine the relationship of trust and learning motivation on learning outcomes of simulation and digital communication in class X students. The results of data analysis showed confidence with the learning outcomes ie r count> r table (0.273> 0.113), there is a positive and significant relationship and continued with t-test> t table (4,437> 1,960), The first hypothesis is accepted, learning motivation with learning outcomes is r count> r table (0.366> 0.113), there is a positive and significant relationship and continued with t-test> t table (2,272> 1,960), the second hypothesis is accepted, self-confidence and motivation to learn with shared learning outcomes. the result is r count> r table (0.2733> 0.161), a positive and significant relationship and continued with the F-count test> FT table (12.33> 1,750)